Why does digital violence against LGBTI people in Thailand and Taiwan continue even after marriage equality? - Amnesty International (Amnesty International, 2025)
Thailand and Taiwan are hailed as champions of the rights of LGBTI people in Asia, as the only two places in the region to legalize same-sex marriage. However, rights won at the registry office do not always translate into safety online. Digital violence continues to threaten LGBTI people, undermining their human rights and progress made. Thai and Taiwanese authorities must do more to combat it.